Relationship between placental alkaline phosphatase activity and cord blood glucose, albumin and neonatal birth weight at term. - Onyesom, Innocent; Olukemi Opajobi, Adefunke; Enyinanya Uzuegbu, Ugochukwu; Oriero, Denis; Mordi, Joseph; Ejiro Awhin, Prosper; Timothy, Enaholo (Investigación Clínica, 2013)
Â  It has been observed that placental alkaline phosphatase (PAP) activity progressively rises as pregnancy advances, possibly, because of its increasing synthesis by placental tissue. The present investigation therefore, examines the relationship between placental alkaline phosphatase activity and the biochemical indices of foetal nutrition (cord blood glucose, albumin) and growth (neonatal birth weight). Placental and umbilical cord blood samples were collected from one hundred and five deliveries and prepared for both, placental alkaline phosphatase assay and glucose and albumin estimations using standard procedures. The birth weights of the neonates at term were taken and recorded. Correlation analyses of the data obtained show signifi- cant positive relationships between PAP and cord blood glucose (r2 = 0.86, p < 0.05), albumin (r2 = 0.71, p < 0.05) and birth weight (r2 = 0.68, p < 0.05), but no significant relationship with gestational age. PAP may be essential in nutrient mobilization to the foetus. However, further studies involving more subjects and an intrauterine growth retardation control group (IUGR) are required to fully document the present report.